Osteological research on the genus Kentropyx from Argentina and revalidation of the specific status for Kentropyx lagartija (Gallardo, 1962) (Squamata: Teiidae) - Tedesco, María Esther (1997)
Cranial and post-cranial osteological characters of specimens belonging to western and eastern populations of Kentropyx viridistriga have been studied. Results of this research point out significant clear-cut morphological differences, in agreement with former studies of the Authors on exo-somatic characters of the same population samples. A subspecific status for western and eastern populations of K. viridistriga is then untenable, and in accordance with the lack of intergradation in their intermediate Chacoan contact area, a specific status for Kentropyx lagartija (Gallardo, 1962) as “evolutionary species” (sensu Frost and Hillis, 1990) is revalidated.